ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN PADA PT MIKA ANUGRAH UNGGUL - AAN NURHADI (JURNAL ILMIAH SIMANTEK, 2023)
The purpose of this study is to show the company's financial ratios PT. Mika Anugrah Unggul. Consisting of: liquidity ratio (Current Ratio, Quick Ratio, Cash Ratio), activity ratio (Inventory Turn Over, Fixed Asset Turn Over, Total Assets Turn Over), solvency ratio (total Debt to Total Asset, Total Debt to Equity Ratio), and profitability ratios (Net Profit Margin, Return on Investment, Return on Equity). The type of research conducted is descriptive research. The focus of the research is the company's financial statements, which consist of a balance sheet, and income statement for the period 2020-2022. The research was conducted through the financial report of the company. The data source used is secondary data. The data collection technique used in this research is documentation. The data analysis used in this research is descriptive analysis using financial ratio analysis. The results of the analysis of financial ratios consisting of liquidity ratios, solvency ratios, activity ratios, and profitability ratios for the 2020-2022 period.